Job Satisfaction and Employee Loyalty: A Causal Relationship Examined with the Use of Structural Equation Modelling - Lotko, Aleksander; Lotko, Małgorzata; Popek, Stanisław; Szałas, Grzegorz; Popek, Adam (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2025)
Objective: Identification of the impact of job satisfaction on employee loyalty. Research Design & Methods: A quantitative approach was applied. Critical analysis of literature and an expert panel was used to identify variables. A questionnaire study was carried out online on the sample of 419 administrative and office employees. Structural equation modelling was used to examine the existence of the assumed relationship. Findings: It has been proved that job satisfaction is a multidimensional construct. It is composed of three elements: 1) career development including the possibilities of training, development, realisation of passions and non-pay benefits, 2) physical job conditions including ventilation, bathrooms, social back office, noise and temperature level, as well as ergonomic standards of equipment, aesthetics of the workplace and 3) interpersonal relations covering relations with co-workers and supervisors, as well as social communication in the workplace. Each of these dimensions turned out to impact employee loyalty and this impact is statistically significant on a level α = 0.001. The strongest impact occurs in case of the two intangible factors: career development (1.024), then interpersonal relations (0.902). For physical working conditions the impact is noticeably weaker (0.211). Implications / Recommendations: It turned out that employee loyalty is strongly impacted by the intangible factors of the work environment. This observation may constitute an important human resources management tool for managers and in particular in the process of motivating the employees. Contribution: Confirming the assumed relationship between the revealed dimensions of job satisfaction and employee loyalty with the use of a sophisticated multidimensional statistical analysis.